Synergy of Organizational Citizenship Behavior, Employee Commitment, and Leader-Member Exchange in Improving Performance Through Organizational Trust at Election Commission: Sinergi antara Perilaku Kewarganegaraan Organisasi, Komitmen Karyawan, dan Pertukaran Pemimpin-Anggota dalam Meningkatkan Kinerja Melalui Kepercayaan Organisasi di Komisi Pemilihan Umum - M. Yusuf Alfian Rendra Anggoro KR; A. Nur Fitrianti (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2025)
This research aims to examine the impact of Organizational Citizenship Behavior (OCB), Employee Commitment, and Leader-Member Exchange (LMX) on employee performance, with Organizational Trust acting as a mediating variable, among staff of the General Election Commission across South Sulawesi. The study employed both descriptive and explanatory survey methods, using a cross-sectional design. The target population consisted of 448 employees from the provincial and district/city-level General Election Commissions across 24 regions in South Sulawesi. A proportional random sampling technique based on regional distribution was applied, resulting in a sample of 211 respondents, determined through the Slovin formula. Data analysis was conducted using Structural Equation Modeling (SEM) with the assistance of AMOS software. The findings revealed that: (1) OCB significantly and positively influences Organizational Trust; (2) Employee Commitment has a significant and positive effect on Organizational Trust; (3) LMX positively affects Organizational Trust; (4) OCB significantly enhances employee performance; (5) Employee Commitment also exerts a significant positive influence on performance; (6) LMX does not have a direct significant effect on performance; (7) Organizational Trust significantly influences performance; (8) OCB contributes positively to performance indirectly through Organizational Trust; (9) Employee Commitment positively impacts performance through Organizational Trust; (10) LMX exerts a significant indirect effect on performance mediated by Organizational Trust.